Dual associations of gut and oral microbial networks with kidney transplantation - Siming Qu; Yuzheng Gu; Xiaoxue Hou; Min Wei; Mengmeng Wang; Yuya Su; Yinglei Miao; Jinlong Yang; Yang Sun; Zhong Zeng (mSystems)
ABSTRACT Gut and oral microbiomes play an essential role in the occurrence and development of kidney disease, but their changes after kidney transplantation in patients with end-stage renal disease and their relationships with host health remain unclear. Through shotgun metagenomic sequencing of fecal and saliva samples, we found that for both gut and oral microbiome, the initial loss of species diversity after kidney transplantation led to a reduction in network nodes and interactions, but strengthened the connections among the remaining species, which started to get a recovery approximately 7–14 days later. Different network modules tended to exhibit unique functions and showed different responses to transplantation. These network changes were significantly correlated with clinical indicators, especially with estimated glomerular filtration rate, suggesting that microbial networks contributed to regulating kidney function and host health from dual dimensions. Our study provides novel insights into associating microbiomes with patient recovery after kidney transplantation and offers new diagnostic strategies.IMPORTANCEUnderstanding the dynamics of gut and oral microbiomes after kidney transplantation is crucial for improving post-transplant outcomes and managing potential complications. Through shotgun metagenomic sequencing of fecal and saliva samples from patients following kidney transplantation, our study emphasizes that, in addition to focusing on the various microbial species themselves, the topological properties of gut and oral microbial networks are also critically important for kidney function. We aim to explore the relationship between host health and the oral and gut microbiomes following kidney transplantation from an ecological perspective and extend to other diseases to advance the study of the microbiome and its clinical impact.